Development e-module on genetic materials to enhance student’s critical thinking skills - Anjani, Fullaikhah; Fatmawati, Umi; Ariyanto, Joko (Biosfer: Jurnal Pendidikan Biologi, 2024)
Genetic material is classified as material that is difficult for students to understand because the material is abstract, there are many foreign terms, and there are many complex molecular reactions, so students have difficulty developing critical thinking skills. Therefore, developing a good, suitable, effective, and attractive media is necessary. . This study aims to develop an e-module on the topic of genetic substance, to test the feasibility of the e-module, and to determine the differences in critical thinking skills before and after the implementation of the e-module. This type of research is research and development research with a 4D Thiagarajan model consisting of define, design, development,and disseminate. . This research was conducted without the dissemination stage. The results of the validation of media experts are 81.7% (fair enough) and material experts are 85.5% (very feasible). The results of the trial were limited to 10 students, namely 92.1% (very decent) and 80.4% biology teachers (quite decent). The results of field trials are 90.2% (very feasible). The results of the t-test indicate that there are differences in critical thinking skills before and after the implementation of the e-module. This study implicate that e-modules on the topic of genetic substances are feasible to use and to empower students’s critical thinking skills.